Infectious mononucleosis, other infections and prostate‐specific antigen concentration as a marker of prostate involvement during infection. Issue 9 (21st January 2016) - Sutcliffe, Siobhan; Nevin, Remington L.; Pakpahan, Ratna; Elliott, Debra J.; Langston, Marvin E.; De Marzo, Angelo M.; Gaydos, Charlotte A.; Isaacs, William B.; Nelson, William G.; Sokoll, Lori J.; Walsh, Patrick C.; Zenilman, Jonathan M.; et al.
Abstract : Although Epstein‐Barr virus has been detected in prostate tissue, no associations have been observed with prostate cancer in the few studies conducted to date. One possible reason for these null findings may be use of cumulative exposure measures that do not inform the timing of infection, i.e ., childhood versus adolescence/early adulthood when infection is more likely to manifest as infectious mononucleosis (IM). We sought to determine the influence of young adult‐onset IM on the prostate by measuring prostate‐specific antigen (PSA) as a marker of prostate inflammation/damage among U.S. military members. We defined IM cases as men diagnosed with IM from 1998 to 2003 ( n = 55) and controls as men without an IM diagnosis ( n = 255). We selected two archived serum specimens for each participant, the first collected after diagnosis for cases and one randomly selected from 1998 to 2003 for controls (index), as well as the preceding specimen (preindex). PSA was measured in each specimen. To explore the specificity of our findings for prostate as opposed to systemic inflammation, we performed a post hoc comparison of other infectious disease cases without genitourinary involvement ( n = 90) and controls ( n = 220). We found that IM cases were more likely to have a large PSA rise than controls (≥20 ng/mL: 19.7% versus 8.8%, p = 0.027; ≥40% rise: 25.7% versus 9.4%, p = 0.0021), as were other infectious disease cases (25.7% versus 14.0%, p = 0.020; 27.7% versus 18.0%, p = 0.092). These findings suggest that, in addition to rising because of prostate infection, PSA may also rise because of systemic inflammation, which could have implications for PSA interpretation in older men. Abstract : What's new? The discovery of Epstein‐Barr virus (EBV) in neoplastic prostate tissue raises questions about the relevance of EBV infection in prostate cancer development. EBV is the major cause of infectious mononucleosis (IM), symptoms of which are most apparent in adolescents and young adults. This study of U.S. military members shows that young‐adult (ages 18‐25) onset IM is associated with a rise in prostate‐specific antigen (PSA) levels during or following infection. Other systemic infections (e.g., influenza) were also linked to increases in PSA. The findings could have implications for the interpretation of PSA screening results.